Bilateral squat asymmetry in surfing athletes - Lundgren, L.; Secomb, J.; Tran, T. T.; Farley, O.; Nimphius, S.; Newton, R. U.; Sheppard, J. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Surfing athletes (SA) have an asymmetrical stance while surfing, which may cause these athletes to prefer an asymmetrical posture. Previous studies have found about 6% imbalance on average regarding ground reaction force (GRF) among college athletes (Flanagan and Salem, 2007; Newton et al., 2006), and that bilateral squat asymmetry can be corrected (McGough et al., 2010). This study investigated bilateral asymmetry for SA and compared between left and right side, front and rear side and between groups of athletes, such as divisions and training status. Methods: Athletes (n=26) from four division based groups, i.e., male and female professional seniors (n=8 and 3, age: 24.5±3.2 and 25.8±6.6 y respectively) and juniors (n=8 and 7, age: 16.0±1.3 and 15.8±0.7 y) performed bilateral squats with their stance split between two force plates (Fitness Technology, Adelaide) recording at 600 Hz. The athletes performed 10, first without any external load (BW) and secondly with an external load (EL) corresponding to 25% of their BW. From the average force of the left and right side a symmetry index (SI) was calculated (McGough et al., 2010). Comparison between SA who strength trained regularly (n=11) versus inconsistently (n=15) was performed using independent t-test. Bilateral asymmetry between feet was analysed using paired t-test. Results: The average SI for all SA was 6.8±4.4% and 8.2±5.8% for the BW and EL squat respectively. There was no significant preference for the front or rear stance leg (p=0.19), or the left or right (p=0.14). Of all SA, 9 athletes had a SI >5% to the rear leg, 6 had a SI >5% to the front leg, and 11 SA were within 5%. The group of female junior surfers (n=7) had a larger average SI than that of the other groups averaging 10.5±4.2% and 10.9±5.7% for the BW and EL conditions (p.0.01). Of these, 5 preferred their back foot and 2 their front foot. Those who had been strength training regularly during the past six months had a lower SI (3.5±2.7%) compared to the other athletes (9.4±4.5%, p.0.001). Discussion: The result of this study suggests that there are bilateral asymmetries in the squat movement for most SA, similarly to that identified in previous research, however larger for the group of female juniors. The asymmetry seems to be minimized in those performing regular lower body strength training exercises. The hypothesis that most surfing athletes would prefer their rear stance leg more than the front turned out to be unconfirmed in this study.